La Revisoría Fiscal frente a la corrupción en el sector salud caso de estudio Hospital Raúl Orejuela Bueno E.S.E (2023)
The functions that over timehavebeengranted to theFiscalAuditor inhis performanceasacontrolandsurveillancebodyinhisdutiesofaccountingreview,compliance audit, is toreport anddenouncesuspiciousoperations inthedevelopmentofhiswork (Jimenez,2021),underthispanoramatheinvestigationthatwascarriedoutwithanexplorative descriptiveapproach,placingasacasestudytheHostitalOrejuelaBuenoE.S.E, inthese momentswherethecrisisoftheGeneralSystemofSocialSecurityinHealthisevident,the roleplayedbytheRevisoriainitspreventivefunctionbecomesrelevanttomitigatetheevents ofcorruptionthatmayoccurwithintheinstitutions